EFEK ANALGETIK KOMBINASI EKSTRAK BUAH BELIMBING WULUH (Averrhoa bilimbi L) DAN EKSTRAK DAUN PEPAYA (Carica Papaya L.) PADA MENCIT (Mus musculus) - Amran Nur (As-Syifaa Jurnal Farmasi, 2018)
Starfruit fruit (Averrhoa bilimbi L.) and papaya (Carica papaya L.) containing the same are flavonoids which have activity as an analgesic. Flavonoids in both plants are thought to function as analgesics because they can inhibit prostrglandin synthesis which results in no release of pain meditors. The purpose of this study was to determine the analgesic effect on extract of starfruit fruit, papaya leaf extract , and a combination of both. starfruit fruit and papaya leaves macerated using 70% ethanol. Examining the analgesic activity of both extracts and combinations using a dose of 500 mg / kg BB. If the weight of the mice is 20 g/BB then the dose variation is 1 mg / 20 g BB. For the combination of the two extracts, it was made a comparison of extracts of starfruit fruit : papaya leaf extract 1: 3, 2: 2, and 1: 3. The first group was given CMC N a 0.5% as a negative control, the second group was given mefenamic acid as a positive control, the group was then given extract test solution as an extract control. After 30 minutes, 1 % acetic acid-inducing induction was given then observed mice stretching. The results showed that the fruit extract inasi komb starfruit: papaya leaf extract 1: 3 has the most excellent analgesic activity diba nding extract activity alone or in combination other.